Universal Particulars towards Maternal Health Circumstance - Sharma, Sushil (Journal of Health Promotion, 2019)
Maternal health is a crucial health problem in developing countries, especially in low resource settings, rural and poor communities. The main aim of this paper is to critically evaluate and explore the situation of maternal health care in Nepal. After reviewing the literature, I found that there are several direct and indirect causes as well as affecting factors in regarding maternal death in developing and least developed countries. In developing countries, women have been facing different problems during pregnancy and delivery period. Knowledge of maternal health and assessable health facilities are most essential in rural areas to save mothers from preventable maternal death.